Scaffolding for assessment success: using gradual release of responsibility to support resident transition to competency-based medical education - Pero, Rebecca P.; Marcotte, Laura (Revue canadienne de l’éducation médicale, 2019)
In competency-based medical education (CBME), assessment is learner-driven; learners may fail to progress if assessments are not completed. The General Internal Medicine (GIM) program at Queen’s University uses an educational technique known as scaffolding in its assessment strategy. The program applies this technique to coordinate early assessments with specific scheduled learning experiences and gradually releases the responsibility for assessment initiation to residents. Although outcomes of this innovation are still under investigation, we feel it has been valuable in supporting resident assessment capture and timely progression through stages of training. Other residency training programs could easily implement this technique to support the transition to Competency by Design.